2021
DOI: 10.1302/2633-1462.212.bjo-2021-0116.r1
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of elective spine surgery during the first wave of COVID-19

Abstract: Aims With resumption of elective spine surgery services in the UK following the first wave of the COVID-19 pandemic, we conducted a multicentre British Association of Spine Surgeons (BASS) collaborative study to examine the complications and deaths due to COVID-19 at the recovery phase of the pandemic. The aim was to analyze the safety of elective spinal surgery during the pandemic. Methods A prospective observational study was conducted from eight spinal centres for the first month of operating following rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Evidence from the early phases of the ongoing COVID-19 pandemic suggests that routine and emergency spine procedures were significantly impacted by provisions and shifts in allocation of in-hospital resources toward COVID-19 care. 1 2 3 4 5 6 7 A comprehensive assessment of the true influence the pandemic has been having on surgical spine care is limited mainly by a lack in long-term observations from later phases of the pandemic on a nationwide level. We therefore designed this study to examine potential changes in the delivery of spinal fusion procedures for spinal infections (SI), such as spondylodiscitis and vertebral osteomyelitis, during the first four waves of COVID-19 in Germany.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from the early phases of the ongoing COVID-19 pandemic suggests that routine and emergency spine procedures were significantly impacted by provisions and shifts in allocation of in-hospital resources toward COVID-19 care. 1 2 3 4 5 6 7 A comprehensive assessment of the true influence the pandemic has been having on surgical spine care is limited mainly by a lack in long-term observations from later phases of the pandemic on a nationwide level. We therefore designed this study to examine potential changes in the delivery of spinal fusion procedures for spinal infections (SI), such as spondylodiscitis and vertebral osteomyelitis, during the first four waves of COVID-19 in Germany.…”
Section: Introductionmentioning
confidence: 99%
“…Since the initial peak of the pandemic, national restrictions on surgical procedures have loosened, and elective cases have largely been resumed, in conjunction with several studies supporting the safety of this trend. In a prospective observational study, Mohammed et al demonstrated that with diligent adherence to national guidelines and COVID-19-secure pathways, elective spine surgery can safely be restored while avoiding viral transmission and without increasing the risk of complications ( 17 ). Manuia et al showed that common operating room procedures do not increase the risk of symptomatic COVID-19 infection ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…The existing literature covering the impact of the COVID-19 pandemic on spinal surgery mainly focusses on the changing neurosurgical workload (i.e., numbers of referrals, emergency attendances, surgeries performed), infection rates, and the efficacy of COVIDrelated implementations within the service 2,3,9,[11][12][13]35,41,44,[46][47][48][49] . Spinal surgery case volume was reported to have decreased by 52-70% over the pandemic 10,35 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…38 When elective surgery was permitted to resume, the NHS created specific guidelines 43 to ensure the continuation of quality elective surgical services as well as prioritize the safety of patients and staff. 44 These included prioritizing appropriate patients, preoperative reverse transcription polymerase chain reaction (RT-PCR) test, self-isolation for 14 days, and dedicated operating theaters for elective operations. 44…”
Section: Covid-19 Pandemicmentioning
confidence: 99%
See 1 more Smart Citation